Ketersediaan Rekam Medis di Rumah Sakit Islam Jakarta Sukapura - Gina Sonia; Lily Widjaja; Deasy Rosmala Dewi; Puteri Fannya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
The medical record is an administration system that records all diagnoses and actions followed by the storage of medical records. Medical record retrieval is an important part to support the effectiveness of services in providing medical records for patients who return to the hospital. This research method uses quantitative descriptive and data collection techniques by observation, interviews and literature study. Based on the results of the research, the filing officer of the Islamic Hospital of Jakarta Sukapura often faced problems during retrieval, the results of the study found that 17 (3.4%) medical records were not found and 26 (5.2%) medical records were misplaced. Factors inhibiting the implementation of medical record retrieval include man factors such as the educational background of officers and the habitual factor of officers who do not use tracers when carrying out medical record retrieval that is not in accordance with SPO at the Islamic Hospital of Jakarta Sukapura. The money factor does not affect the implementation of medical record retrieval. The machine factor is the SMART system for medical record data entry that comes off the shelf. The method factor is that the standard operating procedure for retrieval of medical records is not fully appropriate. The material factor is the absence of loan receipts.